FAKTOR-FAKTOR YANG MEMPENGARUHI SENJANGAN ANGGARAN DI PEMERINTAH DAERAH - Fadli, Fadli (JURNAL FAIRNESS, 2015)
This study aims to: examine the influencing of participatory budgeting, budget goal clarity, and organizational commitment on budgetary slack of government agency unit. A total of 172 officials of echelon 2, 3, and 4 of government agency unit were selected as a sample of this study. The data used in this study are primary data by collecting data through questionnaires. The study found that participatory budgeting, budget goal clarity, and organizational commitment negatively affect budgetary slack of government agency unit. This findings imply that the government agency unit budget slack could be reduced since those organization provide budget by involving all official mainly echelon 2, 3 and 4, defined clearly organization goal, and higher organization commitment.